(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The state is viewed by citizens as like a father, as the father is responsible for all his children, and when the father takes care of one without the other, The other may feel injustice and destabilize his roots towards his country. This injustice created a gap between the public and private sectors, and then that gap widened in light of successive problems. There is a general and cumulative economic problem that began years ago and crystallized after the pandemic, the change in the exchange rate and the rise in food prices from its origins. There is a general and cumulative economic problem that began years ago and crystallized after the pandemic The change in the exchange rate and the rise in food prices from its origin, and this problem may Its harm will be on the unemployed, those working in the private sector for earning, and small employees, And everyone is now waiting for treatment from the father (the state) When studying the population pyramid known to any country with other variables that are associated with it, you begin to study the relationship between the population pyramid and the age structure to determine the size of the available human forces and study the size of unemployment, dependency, etc. The idea of ​​the research is based on having a helicopter treatment on the Iraqi population pyramid, but in a different way.